The Influence Of Room Head Supervision On Handover Effectiveness: Literature Review (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
Background: Handover is the process of transferring patient care responsibilities from one shift to the next. This process is important to ensure continuity of patient care and prevent medical errors. Supervision of the head of the room plays a very important role in the implementation of handover in the nursing department, and this is not only limited to supervision, but also includes aspects of coaching, monitoring and development for staff. Method: This research is a research using the literature review method of searching and compiling PICO analyzing 6 articles between 2018-2023 using the help of keywords, supervision and handover Results: The findings from the 6 articles resulting from the discussion show that there is an influence between the supervision of the head of the room and the handover because the better the supervision is carried out, the more effective the handover is < ). Conclusion: Supervision of the head of the room has a significant influence on the effectiveness of patient handovers. Supervision helps improve nurses' communication, knowledge, skills and motivation for successful handover Suggestion: The Head of the Room needs to periodically supervise the implementation of patient handovers..